2019
DOI: 10.1088/1361-6463/ab3553
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the plasmonic fields by a high refractive index dielectric coating for surface enhanced spectroscopies

Abstract: For stabilization and functionalization, plasmonic nanoparticles (NPs) are often coated with dielectric shells, yet suffer from the weakening of local electric field enhancement. Herein, we numerically demonstrate that, instead of being weakened, the local electric fields can be further enhanced using an appropriate high refractive index dielectric coating. Because the high refractive index dielectric shell owns strong Mie resonances that can participate in the bonding plasmon hybridization, it can avoid exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The basic Mie resonances of a sphere include electric and magnetic dipole, quadrupole, octupole, and higher order modes. [ 51–53 ] For simplicity, these electric resonant modes are marked with E 11 , E 12 , and E 13 while magnetic ones are M 11 , M 12 , M 13 , and so on in a similar fashion. The results of multipole decomposition are presented beneath the total scattering spectra in Figure 2d–f.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic Mie resonances of a sphere include electric and magnetic dipole, quadrupole, octupole, and higher order modes. [ 51–53 ] For simplicity, these electric resonant modes are marked with E 11 , E 12 , and E 13 while magnetic ones are M 11 , M 12 , M 13 , and so on in a similar fashion. The results of multipole decomposition are presented beneath the total scattering spectra in Figure 2d–f.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50] The basic Mie resonances of a sphere include electric and magnetic dipole, quadrupole, octupole, and higher order modes. [51][52][53] For simplicity, these electric resonant modes are marked with E 11 , E 12 , and E 13 while magnetic ones are M 11 , M 12 , M 13 , and so on in a similar fashion. The results of multipole decomposition are presented beneath the total scattering spectra in Figure 2d-f. Clearly, the scattering peaks of the TiO 2 and ZnO core that stick out above the baseline originate from the magnetic Mie resonances which, in turn, are M 11 , M 12 , and M 13 modes from long wavelength to short wavelength.…”
Section: Optical Properties Of Dielectric-pt Core-satellite Nanostructuresmentioning
confidence: 99%
“…Similarly, it has been shown that though the presence of dissipation reduces the field enhancement that may be attained at resonance on the surface of plasmonic particles, this limit may be overcome if they are protected by a dielectric that has a coexisting Mie resonance. [43] Arrays of metallic cores coated by semiconductors may also display negative index of refraction as an electric dipole plasmonic resonance might coexist with a magnetic dipole Mie resonance. [44][45][46] The study of these coupled plasmonic-Mie resonances requires accounting at least for a core, a coating, and the ambient.…”
Section: Doi: 101002/pssb201900560mentioning
confidence: 99%
“…A numerical study of metasurfaces would require at least three materials corresponding to the particles, the substrate, and the ambient. Similarly, it has been shown that though the presence of dissipation reduces the field enhancement that may be attained at resonance on the surface of plasmonic particles, this limit may be overcome if they are protected by a dielectric that has a coexisting Mie resonance . Arrays of metallic cores coated by semiconductors may also display negative index of refraction as an electric dipole plasmonic resonance might coexist with a magnetic dipole Mie resonance .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, localized surface plasmon resonance (LSPR) and the related physical phenomenon have received tremendous research attention due to the extensive optical manipulation and utilization of sensor applications in surface science. With the successful establishment of a nanostructure where local electric field intensity enhanced significantly (10 4 –10 9 enlarged magnitudes), LSPR enhancement is considered to be effective in near-field manipulation upon illumination and induces remarkable surface-enhanced Raman scattering (SERS). As has been widely demonstrated, the excitation and modulation of LSPR are not only related to the dielectric constant of the selected materials or the surrounding environment but also greatly dependent on the morphology, structure, and interparticle coupling of the nanostructures. To effectively enlarge the LSPR enhancement degree, and thus gain outstanding SERS performance, researchers have put great efforts in designing nanostructures with enhanced intensified electromagnetic fields, that is, the “hot spots”. Generally, the more the hot spots in the micronanostructure, the stronger the SERS signal generated from the substrate. In addition, the reduction of spacing between the adjacent structures and the ratio of the interparticle gap to the diameter could significantly enhance the local hot spots intensity of the SERS-active substrate, endowing further enhanced performance of the nanostructure with given hot spots quantity.…”
Section: Introductionmentioning
confidence: 99%